A New Coding Scheme for UMP and JSCC in Short-Packet Communications - Yao, Xinyuanmeng; Ma, Xiao (IEEE communications letters, 2023)
This letter proposes a new coding scheme for short-packet communications, where the messages are encoded successively at the transmitter by a classified enumerative (CE) coding, a cyclic redundancy check (CRC) coding and a polar coding, and then recovered reliably at the receiver by a triple-check hypothesis testing decoding. The proposed scheme can be applied not only in an unequal message protection (UMP) scenario, where different classes of messages have different reliability requirements, but also in a joint source-channel coding (JSCC) system. To evaluate the performance of the JSCC, we present the weighted dependence testing (DT) bound, which is then exploited as a criterion for classifying messages. Simulation results show that: 1) Our UMP coding scheme can provide more error protection for low-entropy messages; 2) Our JSCC scheme can outperform the double polar JSCC scheme and is close to the JSCC DT bound.